WHY PEOPLE SUFFER FROM INSOMNIA - Bokhodirova Madinabonu Bokhodir qizi; Dadabayev Zafar Zakirovich (International Journal of Literature and Language Studies, 2026)
Insomnia is widely recognized as the most common sleep disorder across the world, affecting people of different ages, cultures, and lifestyles. In simple terms, it is not just occasional difficulty sleeping, but a persistent condition that can seriously affect daily functioning and overall well-being. This paper explores the main causes and underlying mechanisms of chronic insomnia by reviewing recent sleep research alongside established psychological theories. It brings together findings from clinical studies, neurobiological research, and psychophysiological evidence in order to provide a more complete understanding of the disorder. The reviewed literature suggests that insomnia does not arise from a single cause. Rather, it develops through a combination of heightened central nervous system activity, psychological factors such as stress and anxiety, disruptions in daily routines, and individual vulnerability differences. In other words, it is a condition shaped by both the mind and the body interacting over time. Among different treatment approaches, Cognitive Behavioral Therapy for Insomnia (CBT-I) is consistently identified as the most effective non-pharmacological intervention. Evidence shows that it can reduce excessive brain arousal and improve the stability and quality of sleep.Overall, the findings highlight that insomnia is best understood through a biopsychosocial perspective that connects biological processes, psychological states, and environmental influences. Future research is expected to focus more on personalized treatment approaches and the long-term effectiveness of existing therapies.